Mapping the Neural Substrates of Recent and Remote Visual Imprinting Memory in the Chick Brain - Tiunova, Anna A.; Komissarova, Natalia V.; Anokhin, Konstantin V. (Frontiers in Physiology, 2019)
Social attachment formed by filial imprinting in newborn chicks undergoes a process of memory consolidation that involves rearrangement of its neural storage substrates. In the first 3 hours after imprinting it depends on the integrity of the intermediate medial mesopallium (IMM) and beyond that time on unidentified memory storage structures dubbed S’. To search for the S’ memory system in the chick brain, we mapped and compared patterns of activity induced by retrieval of filial attachment memory before and after this critical transition. Chicks were trained in the visual imprinting task, and their memory was reactivated by imprinting stimulus either 1 h (recent memory retrieval) or 24 h (remote memory retrieval) after the completion of training. Patterns of brain activity were mapped by in situ hybridization to mRNA of an immediate early gene c-fos. We also mapped c-fos expression induced by the first presentation of the imprinting stimulus. Memory retrieval triggered massive c-fos expression in the chick brain both 1 h and 24 h after the end of training. These activity pчatterns mostly coincided with the c-fos expression induced by the first presentation of imprinting stimulus. However, in the hippocampus c-fos induction was observed only after the first exposure to imprinting stimulus but not after memory retrieval. In the IMM, medio-rostral nidopallium/mesopallium, and hyperpallium densocellulare c-fos activation was induced by retrieval of only the remote but not of the recent memory. These c-fos mapping data point to the candidate brain structures for systems reorganization of imprinting memory in chicks.